Model Transformasi Terhadap Budaya Sunda Cageur, Bageur, Bener, Pinter jeung Singer - Purnama, Jellia Puspa; Hermanto, Yanto Paulus (Sekolah Tinggi Teologi Real Batam, 2024)
The Sundanese culture, known as cageur, bageur, bener, pinter, jeung singer, also referred to as Gapura Panca Waluya, is deeply ingrained in the life of the Sundanese community. Unfortunately, Christianity is often perceived as a religion that opposes culture, even compelling individuals to abandon their native traditions. This perception arises because Christianity was introduced to Sundanese lands by European missionaries, who were associated with colonialism, making conversion to Christianity seem like adopting the religion of the colonizers. Through this research, the author aims to answer how the model of transformation for the Sundanese values of cageur, bageur, bener, pinter, jeung singer can be achieved without opposing them but by transforming the existing understanding to help Sundanese Christians experiencing these cultural values. The data collection and analysis technique employed is a literature review. Through this research, the author hopes to ensure that the Gospel can remain relevant and contextual, especially for the Sundanese community, as God uses culture to communicate His plans and wills. Keywords: Sunda; cageur; bener; pinter; bageurAbstrak Budaya Sunda yaitu cageur, bageur, bener, pinter jeung singer, disebut juga dengan Gapura Panca Waluya merupakan budaya yang melekat dalam kehidupan masyarakat Sunda. Sayangnya, kekristenan dianggap sebagai agama yang menentang budaya, bahkan dianggap memaksa seorang untuk meninggalkan budaya asal. Ini disebabkan oleh karena agama Kristen dibawa ke tanah Sunda melalui para misionaris Eropa yang identik dengan penjajah, sehingga memeluk agama Kristen dianggap memeluk agama penjajah. Lewat penelitian ini, penulis bertujuan ingin menjawab bagaimana model transformasi terhadap budaya Sunda cageur, bageur, bener, pinter jeung singer dengan tidak perlu menentang, namun mentransformasikan pengertian yang ada untuk menolong masyarakat Sunda Kristen mengalami nilai budaya tersebut. Adapun teknik pengumpulan dan analisa data menggunakan kajian literatur. Lewat penelitian ini, penulis berharap agar Injil bisa tetap menjadi relevan dan konstekstual khususnya bagi masyarakat Sunda, sebab Allah memakai budaya untuk mengkomunikasikan rencana dan kehendakNya.Kata Kunci: Sunda; cageur; bener; pinter; bageur